Flexible Quasi‐Solid State Ionogels with Remarkable Seebeck Coefficient and High Thermoelectric Properties. Issue 32 (19th July 2019) - Cheng, Hanlin; He, Xu; Fan, Zeng; Ouyang, Jianyong
Abstract: Thermoelectric materials can be used to harvest low‐grade heat that is otherwise dissipated to the environment. But the conventional thermoelectric materials that are semiconductors or semimetals, usually exhibit a Seebeck coefficient of much less than 1 mV K −1 . They are expensive and consist of toxic elements as well. Here, it is demonstrated environmental benign flexible quasi‐solid state ionogels with giant Seebeck coefficient and ultrahigh thermoelectric properties. The ionogels made of ionic liquids and poly(vinylidene fluoride‐ co ‐hexafluoropropylene) (PVDF‐HFP) can exhibit a giant Seebeck coefficient up to 26.1 mV K −1, the highest for electronic and ionic conductors. In addition, they have a high ionic conductivity of 6.7 mS cm −1 and a low thermal conductivity of 0.176 W m −1 K −1 . Their thermoelectric figure of merit (ZT) is thus 0.75. The giant Seebeck coefficient is related to the ion‐dipole interaction between PVDF‐HFP and ionic liquids. Their application in ionic thermoelectric capacitors is also demonstrated for the conversion of intermittent heat into electricity. They are especially important to harvest the low‐grade thermal energy that is abundant on earth. Abstract : Ionogels composed of polymer networks and ionic liquids are prepared and studied for thermoelectric conversion. They can exhibit an ionic Seebeck coefficient up to 26 mV K −1, the highest for electronic and ionic conductors. In addition, they can have high ionic conductivity whereas low thermal conductivity. Thus, they can exhibit a high ZT value of 0.75.